Short RNAs are transcribed from repressed Polycomb target genes and interact with Polycomb Repressive Complex-2 - Kanhere, Aditi (2010)
Polycomb proteins maintain cell identity by repressing the expression of developmental regulators specific for other cell types. Polycomb repressive complex-2 (PRC2) catalyses trimethylation of histone H3 lysine-27 (H3K27me3). Although repressed, PRC2 targets are generally associated with the transcriptional initiation marker H3K4me3 but the significance of this remains unclear. Here, we identify a new class of short RNAs, ~50-200 nucleotides in length, transcribed from the 5′-end of polycomb target genes in primary T-cells and embryonic stem cells. Short RNA transcription is associated with RNA polymerase II and H3K4me3, occurs in the absence of mRNA transcription and is independent of polycomb activity. Short RNAs form stem-loop structures resembling PRC2 binding sites in Xist, interact with PRC2 through SUZ12, cause gene repression in cis and are depleted from polycomb target genes activated during cell differentiation. We propose that short RNAs play a role in the association of PRC2 with its target genes.